2021
DOI: 10.1371/journal.pone.0255628
|View full text |Cite
|
Sign up to set email alerts
|

Integrated care pathways in neurosurgery: A systematic review

Abstract: Introduction Integrated care pathways (ICPs) are a pre-defined framework of evidence based, multidisciplinary practice for specific patients. They have the potential to enhance continuity of care, patient safety, patient satisfaction, efficiency gains, teamwork and staff education. In order to inform the development of neurosurgical ICPs in the future, we performed a systematic review to aggregate examples of neurosurgical ICP, to consider their impact and design features that may be associated with their succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Another alternative path forward is the integration of multidisciplinary care-including mental health resources-directly into spine programs. Multiple studies have demonstrated the positive effects of these programs on the outcomes of patients suffering from both operatively and nonoperatively managed spine conditions, [41][42][43][44] although further study of their impact on mental health specifically is needed.…”
Section: Health Services Researchmentioning
confidence: 99%
“…Another alternative path forward is the integration of multidisciplinary care-including mental health resources-directly into spine programs. Multiple studies have demonstrated the positive effects of these programs on the outcomes of patients suffering from both operatively and nonoperatively managed spine conditions, [41][42][43][44] although further study of their impact on mental health specifically is needed.…”
Section: Health Services Researchmentioning
confidence: 99%
“…A Cochrane review defined five criteria for a clinical pathway to include an organized multidisciplinary plan of care, translation of guidelines to current practice, provides specific steps in a course of care, gives a timeframe, and aims to standardize care for a specific population, problem, or procedure (Youngerman et al, 2019). Implementing a clinical pathway can benefit DBS patients by ensuring they receive interventions in a timely and efficient manner, reducing practice differences, decreasing readmissions, and improving the length of stay and patient satisfaction (Lee et al, 2021). These aforementioned studies show that clinical pathways or ERAS vary greatly across medical institutions.…”
Section: Summary Of the Literaturementioning
confidence: 99%
“…A systematic review of neurosurgery care pathways returns twenty-four clinical pathways with only one functional neurosurgery pathway (Lee et al, 2021). This systematic review shows a lag in functional clinical pathways but may not be all inclusive of the literature given the inclusion criteria used.…”
Section: Gaps In Literaturementioning
confidence: 99%
See 2 more Smart Citations